IL-6 and IL-10 in the serum and exfoliated cervical cells of patients infected with high-risk human papillomavirus. - Camila Mareti Bonin-Jacob; Larissa Zatorre Almeida-Lugo; Marco Antonio Moreira Puga; Ana Paula Machado; Cacilda Tezelli Junqueira Padovani; Mariana Calarge Noceti; Alda Maria Teixeira Ferreira; Carlos Eurico Dos Santos Fernandes; Júlio César Possati Resende; Adriane Cristina Bovo; Inês Aparecida Tozetti (PLoS ONE)
Persistent infection by high-risk human papillomavirus (HR-HPV) is the main cause of cervical cancer and its precursor lesions. While some cytokines help immune cells in virus clearance, others contribute to the persistence of infection and neoplastic progression. Here, the levels of interferon (IFN)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-10, IL-6, IL-4, and IL-2 were quantified in the serum and exfoliated cervical cells (ECCs) of patients with HR-HPV, and the presence of IL-6+ cells was investigated in uterine cervix biopsies. Cytokine levels in the serum and ECCs of 26 HR-HPV DNA-positive patients and 18 HPV DNA-negative patients were measured using flow cytometry. Fifteen uterine cervix biopsy samples embedded in paraffin were subjected to immunohistochemical analysis for the detection of IL-6+ cells. HR-HPV-positive patients showed increased IL-6 and IL-10 in the ECCs and serum, respectively. Compared with HPV DNA-positive patients, HPV DNA-negative patients had higher levels of IL-6 in ECCs. Patients with multiple infections of HPV had higher levels of IL-6 in their ECCs than those with a single infection. Immunostaining of uterine cervix biopsy samples revealed no differences in IL-6 expression between the different classes of histopathological lesions. However, differences were observed in the expression levels of IL-6 and IL-10 at the systemic and local levels in HR-HPV-positive patients without cervical lesions. Considering the functional characteristics of these cytokines, it can be inferred that such patients are prone to persistent HPV infection.